Needs Assessment and Reasons for Consuming Food Supplements for Body-Building and Weightlifting Athletes in Ardabil Province - Nima Hasanzadeh; Mehrdad Moharramzadeh; Abbas Naghizadeh-Baghi (Research in Sport Management and Marketing)
Purpose: The purpose of this study is to assess the needs and causes of dietary supplements for bodybuilding and weightlifting athletes in Ardabil province.Methods: The present study is a descriptive research that was performed as a survey, both qualitative and quantitative strategies were used.  The statistical population of this study consists of 385 athletes in the field of bodybuilding and weightlifting in Ardabil province.  The interviewees were selected using targeted sampling with the participation of 11 of the best respondents to the questions to achieve theoretical saturation. Then, using MAXQDA12 software, the data was coded and the code was used for the researcher-made questionnaire.  The findings showed that most of the supplements consumed by athletes in the study were 95% protein V-concentrate, V-isole protein, casein protein, egg white protein, soy protein, amino protein, and branched-chain amino acids. Results :  According to the results, there is a significant difference in the frequency of need for creatine supplementation among bodybuilding and weightlifting athletes in Ardabil province and the need for creatine supplementation in weightlifting athletes is more than bodybuilding athletes (P = 0.003) (Meaning in other supplements). In other supplements, no significant difference was observed in the two disciplines (P ≥ 0.05).Conclusion:  The most important reasons for consuming dietary supplements in the athletes in the study of consumption are increasing muscle volume, increasing muscle strength, muscle recovery, being antioxidant, reducing fatigue, and burning fat, respectively.